2012
DOI: 10.1038/onc.2011.635
|View full text |Cite
|
Sign up to set email alerts
|

FOXC1 regulates the functions of human basal-like breast cancer cells by activating NF-κB signaling

Abstract: Human basal-like breast cancer (BLBC) is an enigmatic and aggressive malignancy with a poor prognosis. There is an urgent need to identify therapeutic targets for BLBC because current treatment modalities are limited and not effective. The forkhead box transcription factor FOXC1 has recently been identified as a critical functional biomarker for BLBC. However, how it orchestrates BLBC cells was not clear. Here we show that FOXC1 activates the transcription factor NF-κB in BLBC cells by increasing p65/RelA prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 31 publications
3
88
1
Order By: Relevance
“…S2, A and B). Again, no significant change in (17,19). To determine whether changes in cell number could account for the increase in invaded cells, we analyzed changes in cell number of MCF10A and MCF12A cells transduced with GFP control or FOXC1 expressing adenovirus over a 6-day period.…”
Section: Transient Foxc1 Expression Increases Invasion Withoutmentioning
confidence: 99%
See 1 more Smart Citation
“…S2, A and B). Again, no significant change in (17,19). To determine whether changes in cell number could account for the increase in invaded cells, we analyzed changes in cell number of MCF10A and MCF12A cells transduced with GFP control or FOXC1 expressing adenovirus over a 6-day period.…”
Section: Transient Foxc1 Expression Increases Invasion Withoutmentioning
confidence: 99%
“…Although it has recently been suggested that FOXC1 may dictate the BLBC phenotype in part through NF-B signaling (19), the mechanisms utilized by FOXC1 to increase cancer aggressiveness remain to be fully elucidated. Here, we show that transient expression of FOXC1, like the previously reported stable expression of FOXC1 (17,18), increases invasion of nontransformed mammary epithelial cell lines.…”
mentioning
confidence: 99%
“…Forkhead box C1 (FOXC1) is a member of the FOX superfamily of transcription factors that act on gene promoters or interact with other transcription factors to activate transcription (Du et al, 2012;Wang et al, 2012). Furthermore, growing evidence indicates that FOXC1 can also contribute to epithelial-to-mesenchymal transition (EMT), cell signal transduction, and migration of endothelial cells, affecting multiple aspects of the growth cycle and proliferation activities of tumor cells (Chung et al, 2012;Xia et al, 2013;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, growing evidence indicates that FOXC1 can also contribute to epithelial-to-mesenchymal transition (EMT), cell signal transduction, and migration of endothelial cells, affecting multiple aspects of the growth cycle and proliferation activities of tumor cells (Chung et al, 2012;Xia et al, 2013;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The other top features are FOXA1, which has been identified as a tumor suppressor [19] and MLPH, which is not known to be associated with breast cancer, but has an experimentally verified interaction to RAB27A, which was shown to promote proliferation in human glioma cells [20]. Furthermore, we identified FOXC1 as a top feature, which is of the same family of transcription factors as FOXA1 and which was shown to play a role in NF-κB signaling in basal breast cancer cells [21].…”
Section: Analysis Of Misclassification By the Control Modelmentioning
confidence: 89%